Screening of some Indonesian medicinal plant extracts for anti quorum sensing activity to prevent Aeromonas hydrophila infection in Oreochromis niloticus (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Pangastuti A, Sari SLA, Budiharjo A, Fitri ST, Sayekti P, Putri SR. 2021. Screening of some Indonesian medicinal plant extracts for anti quorum sensing activity to prevent Aeromonas hydrophila infection in Oreochromis niloticus. Biodiversitas 22: 3517-3522. Aeromonas hydrophila disease is a threat to Indonesia's aquaculture and fishing industries because of its results in mass deaths. Efforts to treat and prevent A. hydrophila infection in fish have so far been limited to the use of antibiotics. The use of these antibiotics can result in bacterial resistance as well as issues related to fish quality and environment. Another option is to target the bacterial quorum sensing (QS) system, a bacterial intercellular communication system that uses signal molecules, regulates the expression of A. hydrophila virulence factors such as exoprotease enzymes, elastase, and biofilms. The expression of A. hydrophila virulence factor can be inhibited by using QS inhibitor compounds, preventing infection from starting. The purpose of this study was to screen some Indonesian medicinal plant extracts for anti-QS activity and then use the selected extract to prevent A. hydrophila infection in Tilapia fish (Oreochromis niloticus). With the administration of extract, QS inhibition was observed in vitro based on the production of violacein in Chromobacterium violaceum; enzyme exoprotease, elastase, and the formation biofilm in A. hydrophila. Tilapia fishes were fed with extract supplementation and then infected with A. hydrophila in an in vivo infection challenge test. These test fishes were divided into six treatment groups given a different concentration of extract in feed (Healthy fish with a concentration of 0 g/100 g of feed as control; infected fish with a concentration of 0 g/100 g of feed; infected fish with a concentration of 0.2 g/100 g of feed; infected fish with a concentration 0.4 g/100 g of feed; infected fish with a concentration of 0.6 g/100 g of feed; infected fish with a concentration of 0.8 g/100 g of feed). Fish were reared for 2 weeks with the frequency of feeding 3 times a day. The variables observed included fish survival rate, behavior (swimming, agility, movement, and frequency of operculum opening), and morphology of the test fish. Data analysis of virulence factors production, fish survival rate, fish appetite, and frequency of operculum opening was carried out using the ANOVA variant test, continued with a 5% DMRT test. Others were analyzed descriptively. Of all the extracts studied, 4 extracts showed inhibition of the production of the violaceum pigment in C. violaceum. Muntingia calabura leaves extract was chosen for further testing due to its ease of availability and safety. The extract was significantly decreased the production of A. hydrophila caseinolytic and elastolytic protease, but had no effect on biofilm formation. In vivo challenge test with A. hydrophila showed better survival rate and fish condition in fish groups that were supplemented with M. calabura extract.
Keywords: Quorum sensing; Aeromonas hydrophila; Muntingia calabura; Tilapia fish